Association between gene polymorphisms in TIM1, TSLP, IL18R1 and childhood asthma in Turkish population. - ÖZKAYA, EMİN; ÖZKAYA, EMİN (My University, 2014)
Many immunologic and inflammatory mechanisms play a role in asthma etiology. The aim of this study was to investigate the susceptibility of asthma patients in the Turkish population with demonstrating genes for polymorphisms in TIM1, TSLP and IL18R1. All of the genomic DNA samples were isolated from blood samples according to a standard salting-out protocol. DNA samples were stored at -20 degrees C until the genotype analysis was performed. rs3806933 (TSLP -847 C > T) and TIM1 -416G > C were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The rs3806933 (TSLP -847 C > T) was genotyped by PCR using our new primers and HphI restriction enzyme digestion. rs2287033 (IL18R1 c. 1270+150 A > G), rs3213733 (IL18R1 c. 626-196 G > T), and rs3771166 (IL18R1-c. 302+1694 C > T) were genotyped using SYBR green dye based real time PCR assay. Results: The allele frequencies of 5 SNPs in TSLP, TIM-1, and IL18R1 genes were determined in 139 asthmatic patients and 126 healthy controls of in Turkish population. The investigated SNPs are as follows; rs3806933 (TSLP -847 C > T), TIM1 -416G > C, rs2287033 (IL18R1 c. 1270+150 A > G), rs3213733 (IL18R1 c. 626-196 G > T), and rs3771166 (IL18R1-c. 302+1694 C > T). Results suggest that IL18R1 c. 626-196 G > T (rs3213733) and TIM1 -416G > C are significantly associated with asthma in patients in Turkish population. Patients with AA genotypes of rs2287033 (IL18R1 c. 1270+150 A > G), have significantly less total serum IgE levels when compared with patients having GG or GA genotypes (p T (rs3213733) and TIM1 -416G > C are significantly associated with asthma patients in Turkish population.